2013
DOI: 10.4103/2141-9248.109457
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practice of Breast Self-Examination among Market Women in Abakaliki, South East Nigeria

Abstract: Background:Breast cancer is the most common female malignancy and commonly associated with high levels of morbidity and mortality in developing countries due to late presentation. Breast self-examination (BSE) can help in early detection of the disease.Aims:This study aims to determine the awareness and practice of BSE among market women in Abakailiki, Southeast Nigeria.Subjects and Methods:This cross-sectional descriptive study involved the use of questionnaire among market women in Abakaliki. Inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 22 publications
3
47
2
Order By: Relevance
“…Findings from this study are similar to what were observed in other studies among market women in Iran and Nigeria [4] [11], where majority of the respondents were below the age of 40 years and were married with secondary and post-secondary education.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Findings from this study are similar to what were observed in other studies among market women in Iran and Nigeria [4] [11], where majority of the respondents were below the age of 40 years and were married with secondary and post-secondary education.…”
Section: Discussionsupporting
confidence: 80%
“…Breast cancer awareness among respondents in this study was very high (88%) and this could serve as an entry point to increase breast cancer education especially on the need for frequent selfbreast examination so as to pick early suspected cases for self-referral to the clinic for assessment and diagnosis. The high level of awareness confirmed what was reported among Market Women in Nigeria, where 78% of the market women were aware of breast cancer [4]. However, these findings contradict what was reported among students in Turkey and Nigeria, where low levels of awareness were reported [41] [45] [46].…”
Section: Discussioncontrasting
confidence: 36%
See 3 more Smart Citations